Enhancing Acehs Fiscal Independence Amid Declining Autonomy Funds - Dawood, Taufiq Carnegie; Bunsit, Thanawit; Madiyoh, Abdulhakim; Farlian, Talbani; Seftarita, Chenny; Fitriyani, Fitriyani (Journal of Accounting Research, Organization and Economics, 2025)
Objective This study aims to analyze what factors can influence fiscal independence in Aceh Province, Indonesia, using annual regency and municipality data from 2010 to 2021.Design/Methodology This research uses a dynamic panel regression model with the Generalized Method of Moments (GMM) estimation method to analyze data. This method is employed to overcome the endogeneity problem and is supplemented with corroborating evidence.Results This study found that poverty negatively affects fiscal independence in Aceh. Furthermore, GRDP and the number of taxpayers positively affect fiscal independence in Aceh. This study also found that public capital expenditure positively affects Aceh's fiscal independence. Furthermore, combined with corroborating evidence, this study concludes that more than increasing the amount of public capital expenditure alone is needed to increase Aceh's fiscal independence. Improving the quality of the provision of facilities and infrastructure financed by public capital expenditure is also vital for increasing Aceh's fiscal independence.Research limitations/implications This study's significant implication underscores the importance of improving the quality of the provision of facilities and infrastructure financed by public capital expenditures to enhance regional fiscal independence, which is in contrast to conclusions in the existing literature.Novelty/Originality The state of the art of this study is, it uses a different approach to analyze the determinants of regional fiscal independence in Aceh Province, Indonesia. It employs the panel Generalized Method of Moments (GMM) method combined with corroborating evidence. To the best of our knowledge, this is the first study which employs panel GMM to study fiscal independence, taking Aceh as a case study.